Psychometric properties of the Icelandic versions of Generalized Anxiety Disorder -7 (GAD-7) and Patient Health Questionnaire – 9 (PHQ-9): sample of 18-25 years old students - Hrafnhildur Snæbjörnsdóttir 1991- (2018)
Psychometric properties indicate the quality of measurements, how reliable and valid they are in measuring a certain construct. Generalized Anxiety Disorder – 7 (GAD-7) and Patient Health Questionnaire (PHQ-9) are brief self-report questionnaires intended to measure symptom severity and screen for Generalized Anxiety Disorder (GAD) and Major Depressive Disorder (MDD). This study aimed to assess the psychometric properties of the GAD-7 and the PHQ-9 in a sample of 292 Icelandic students, aged 18-25 years old. Normative data for these scales is needed in Iceland. Thus, the data from the study could be useful in a collection of normative scores for this age group in Iceland. Exploratory factor analysis indicated a one-factor solution for both scales. The GAD-7 demonstrated excellent internal reliability, adequate convergent validity with high correlation to another measure of GAD but unsatisfactory discriminant validity with a high correlation to measures of different anxiety- and depressive disorders. The PHQ-9 displayed great internal reliability, had some evidence of convergent validity but inadequate discriminant validity whereas it correlated higher with measures of anxiety than depression. GAD and MDD are highly comorbid thus it was expected to see a high correlation between measures of those constructs. Hence, it was problematic to evaluate discriminant validity of PHQ-9 and GAD-7, the scales both correlated highly to measures of different but comorbid constructs. Keywords: generalized anxiety disorder, depression, psychometric properties, GAD-7, PHQ-9